Evolutionary history of Podarcis tiliguerta on Corsica and Sardinia. Issue 1 (December 2017) - Rodríguez, V.; Buades, J.; Brown, R.; Terrasa, B.; Pérez-Mellado, V.; Corti, C.; Delaugerre, M.; Castro, J.; Picornell, A.; Ramon, M.
Abstract Background Podarcis tiliguerta is a wall lizard endemic to the Mediterranean islands of Corsica and Sardinia. Previous findings of high mtDNA and morphological diversity have led to the suggestion that it may represent a species complex. Here, we analysed mitochondrial and nuclear markers (mtDNA, 3110 bp; 6 nDNA loci, 3961 bp) inP. tiliguerta sampled from thirty-two localities across Corsica and Sardinia. Results We find much greater intraspecific genetic divergence than between sister species of other Mediterranean islandPodarcis, i.e., betweenP. lilfordi andP. pityusensis . We detected three mtDNA clusters in Corsica (North, South-East and South-West) and either two or three in Sardinia (North vs. South) depending on the clustering method. Only one or two nDNA groups were identified within each main island (again, depending on the method). A Bayesian time-calibrated multispecies coalescent tree was obtained from mtDNA and provided statistical support for a Miocene origin of the species (13.87 Ma, 95% HPD: 18.30–10.77 Ma). The posterior mean divergence time for the Corsican and Sardinian lineages was 12.75 Ma ago (95% HPD: 16.94–9.04 Ma). Conclusion The results support the evolutionary distinctiveness of Corsican and Sardinian populations and also indicate a lack of post-divergence migration despite periods of contact being possible. Further to this, species delimitation analyses of Corsican and Sardinian lineages provided statistical support for their recognition as distinct (sister) taxa. Our results provide new insights into the biogeography of the Mediterranean biodiversity hotspot, and contribute important findings relevant to the systematics and evolution of this speciose lizard genus.